Revenue Budget Variance and Capital Expenditure Realization Emperical Evidence from Indonesian Local Goverments - Fahlevi, Heru (Jurnal Dinamika Akuntansi, 2017)
This study aims to examine the effect of local revenue variance, variance of fund balances and budget account surplus (SILPA) for capital expenditure realization. The population in this study were all districts / cities in Indonesia, with observations taken from 2010 to 2014 amounting to 508 districts / cities from 34 provinces. Based on the Slovin formula, obtained a sample of 345 districts / cities as observation data. Data obtained from local government budget and budget realization report 2010-2014). Multiple regression analysis applied to data analysis. Empirical results indicate that the variance of local revenue is related to the realization of capital expenditure. The results also reported the relationship between variance of equilibrium funds and capital expenditure realization as well as the relationship between budget account surplus and capital expenditure realization. The results are also related simultaneously between the variance of local revenue, variance of fund balance, and budget account surplus (SILPA) for capital expenditure realization. The conclusions of this study are the variance of local revenue, the variance of fund balance, and the remaining budget have a positive effect on capital expenditure. Thus, local governments can be said to have changed the variance of Regional Income, balance funds and SiLPA to capital expenditures. The consequence is the emergence of new capital expenditure programs that may not be realized.